Correlations between body density measured with anthropometric variables in young boys on pubertal stage - José Fernandes Filho; Rogério Pedro de Barros Pereira (Universidade Federal de Santa Catarina, 2004)
The objective of this study was to identify the correlations between measures of body density and anthropometric variables of 30 young boys in pubescent stage identified by self assessment. The sample was composed by students with mean age (12,3 years / ± 2,26). The variables were analyzed in the SPSS program version.10.0, using Pearson's correlation coefficients (r). High and significant values (p <0,001) were found among all the skinfolds with higher values for the following points: leg (r= - 0,880); thigh (r = -0, 878); suprailiac (r = -0, 823), for growth variables the following values were obtained: age (r = 0,732); stature (r=0,723) and body mass (r= 0,384), for the circumferences more significant value were found: hip (r = -0,880) and among the widths: humerus biepicondilous (r = 0,621). This study provides the need for combining variables to develop new equations for young boys. RESUMO Este estudo teve como objetivo identificar as correlações da densidade corporal mensurada hidrostaticamente e as variáveis antropométricas de 30 jovens meninos no estágio maturacional pubescente identificado através da auto-avaliação. A amostra foi composta por estudantes, com idade média ( 12,3 anos ± 2,26)as variáveis foram analisadas no programa SPSS v.10.0, através coeficiente da correlação de Pearson (r), obtendo-se valores altos e significativos para ( p< 0,001)todas as dobras cutâneas com maiores valores dos seguintes pontos: perna ( r= -0,880 ); coxa (r=-0, 878); suprailíaca ( r= -0, 823), as variáveis relativas ao crescimento físico obtiveram os seguintes valores: idade ( r= 0,732 ); estatura (r= 0,723) e massa corporal (r= 0, 384) o perímetro de valor mais significativo encontrado: quadril ( r= -0,880) e dentre os diâmetros: biepicondiliano de úmero(r= 0,621). Este estudo proporciona então a necessidade de combinações entre as variáveis analisadas afim de obter indicadores para o desenvolvimento de equações no público jovem.